A MoNiO4 flower-like electrode material for enhanced electrochemical properties via a facile chemical bath deposition method for supercapacitor applications. (12th December 2019) - Anil Kumar, Yedluri; Singh, Saurabh; Kulurumotlakatla, Dasha Kumar; Kim, Hee-Je
Abstract : Schematic representation of the synthesis of MoNiO4 flower-like nanostructures. Abstract : Recently, binary metal oxides with the multifunctional properties of nickel foam-based architectures have attracted considerable interest as desirable electrode materials for applications as well capability supercapacitors (SCs). In this study, the MoNiO4 flower-like nanostructure with enhanced supercapacitance performance was successfully synthesized via a chemical bath deposition (CBD) method and subsequent calcination in air. This approach was primarily due to the availability of more surface-active sites in a well-defined hierarchical architecture, which allowed the rapid diffusion of electrolyte ions and minimized the electron transport limitation. The as-fabricated MoNiO4 electrode yielded a maximum specific capacitance of 1140 F g −1 at 2 A g −1, which is comparable to those of the state-of-the-art MoNiO4 electrodes. Moreover, the MoNiO4 material exhibited an excellent energy density of 64.2 W h kg −1 at 2 A g −1, an outstanding power density of 1750 W kg −1, and an excellent electrochemical stability with 97.8% retention after 3000 continuous charge–discharge cycles, even at a high current density of 4 A g −1, which are comparable to those of the state-of-the-art MoNiO4 flower-like structure. The outstanding performance of the MoNiO4 -based flower-like electrode was successfully utilized to drive efficient electrode for SCs applications. Moreover, the electrochemical performance of an unique hierarchically structured MoNiO4 -based binder-free electrode with our facile approach paves a new pathway for the low-cost production of electrodes with the development of novel metal oxides for high-performance SC applications.